Analisis Kebijakan dalam Penanganan Dampak Risiko Covid-19 Terhadap Usaha Mikro, Kecil dan Menengah Di Kota Bandung Jawa Barat, Indonesia - Sam'un Jaja Raharja; Herwan Abdul Muhyi; Rusdin Tahir (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The Covid-19 outbreak has had implications for various areas of life, including health, economics and social. The economic impact is felt by all economic actors. This study aims to analyze the impact of the risk of Covid-19 on Micro, Small and Medium Enterprises (MSMEs) in Bandung City and formulate policy steps for these MSMEs. The research method used in this research is a combination research method, namely quantitative and qualitative methods. Primary data collection techniques through distributing questionnaires to MSMEs business actors during the Pandemic. Secondary data were collected from government reports, mass media news, as well as sources from journals and research reports. The research was carried out from April to July 2020. The results showed the impact of PSBB felt by MSMEs in the form of a decrease in sales of 92%, 77% of demand, an increase in raw material prices of 53%, 48% of financial difficulties, 45% of production constraints, of raw material difficulties 49 % and distribution barriers 38%. The research concludes that the implementation of PSBB in Indonesia is unlikely to be prolonged. The effect of implementation has a direct impact on MSMEs that lose income. The recovery needed by MSMEs is market access. Acceleration of recovery can be done by making policies for the procurement of goods and services supplied by MSMEs. The government is advised to campaign for “spending from MSMEs.” Capital assistance is provided in the form of low-interest loans with a wide payback period for additional working capital needs.